Pembelajaran Cerita Fiksi Sebagai Pendidikan Multikultural pada Siswa Dwibahasa di SMA Taman Rama Jimbaran - Ni Nyoman Mei Artini; I Wayan Rasna; I Nyoman Sudiana (LP. Ma'arif Janggan Magetan, 2024)
This study aims to describe the understanding of multicultural-based fictional stories and teacher strategies in teaching fictional stories as multicultural education for bilingual students at SMA Taman Rama Jimbaran. The method used in this study is descriptive qualitative. Data collection methods that will be used in this study include (a) assignment methods (b) observation, (c) interviews, (d) questionnaires, (e) evaluation methods. Data analysis techniques used in this study are data collection, data reduction, data presentation, drawing conclusions. The results show that learning multicultural-based fictional stories (tales, dramas, and novels) has been effective in increasing the awareness of bilingual students at SMA Taman Rama Jimbaran towards cultural diversity. Students are able to understand cultural values, such as local traditions, morality, and social dynamics that reflect cultural diversity. Students' ability to understand the fictional stories given depends on the level and background of the students. Students with a Balinese cultural background and understand Indonesian tend to find it easier to understand the contents of the text than students outside of Balinese culture. Students who are at a lower level, some are not yet able to express their thoughts well, and the use of vocabulary is less diverse. Teachers use a variety of approaches according to grade level, such as visual media, group discussions, and rewards to increase student engagement. These strategies have successfully strengthened students' literacy skills and their awareness of multicultural values.